Pemberdayaan kelompok tani kedelai melalui penerapan teknologi pengolahan kedelai untuk meningkatkan pendapatan petani di Desa Marga Mulya Kecamatan Rantau Rasau - Lizawati Lizawati; Elis Kartika; Made Deviani Duaja; Hajar Setyaji; Gusniwati Gusniwati (Riau Journal of Empowerment, 2021)
The aim of the community service activiy is to increase farmers’ knowledge and income in diversiying soybean processed products. This activity was carried out in Marga Mulya village, Rantai Rasau district, Tanjung Jabung Timur regecy which held from June until December 2019. The method used in this activity is giving education to society through the process of learning and implementation participatory (participatory learning and action), stages taken are; counseling on post-harvest technology for soybeans, practicing and implementing of making flour and soybean powder alongside with its processed products and enhancing packaging. Evaluation had done in the beginning of activity, the evaluation criteria are the number of attendance and the percentage of how active the member of farmers group in each stage. The result of this community service activity shows that most (80%) of farmer group partner undestand and able to use soy processing tool and also to create variety of soybean processed product. It shows the increment of PKM business in achieveing diversiying processed soybean products, increaseing of processed production and product resilicence, as well as rising added value of processed soybean products.